The use of convalescent plasma therapy and remdesivir in the successful management of a critically ill obstetric patient with novel coronavirus 2019 infection: A case report - Jonathon Anderson; Jordan Schauer; Suzanne Bryant; Cornelia R. Graves (Elsevier, 2020)
Summary: Remdesivir is a novel therapeutic with known activity against SARS CoV-2 and related coronaviruses. Remdesivir, as well as convalescent plasma therapy, are currently under investigation as potential therapies for patients with Coronavirus Disease 19 (COVID-19). In this case report we summarize the use of convalescent plasma therapy and then remdesivir as a late addition in the treatment of a critically ill obstetric patient with COVID-19. The patient subsequently improved, was extubated 5 days after initiation of remdesivir, was transitioned to room air 24 h later, and discharged at the completion of remdesivir therapy.